The effect of manganese IV oxide doping on the optical and elastic properties of calcium borate glass derived from waste chicken eggshell - A.S., Asyikin; A.A., Shamimi; S.N., Nazrin; M.K., Halimah; Boukhris, Imed (Elsevier BV, 2021)
The extraction of CaO from waste eggshell can be used to produce new product known as calcium borate glass doped manganese (IV) oxide. A tertiary (B2O3)0.6 [(CaO)0.4]1-x (MnO2)x glass system with 0.010 ≥ x ≥ 0 M fraction were prepared using conventional melt-quenching technique. XRF spectroscopy confirms CaO as the main constituent in the calcined eggshell. XRD spectra unveils the two amorphous humps of the glass samples. FTIR analysis reveals the typical features of CaCO3 and B2O3 network. The density has opposite behaviour with molar volume as MnO2 content increases. Next, the optical band gap and refractive index are evidencing the formation of non-bridging oxygen in the glass matrix. The present glass system also has low polarizability, acidic in nature and have tendency to metallizing. The elastic properties of glass samples were determined using the ultrasonic technique. Elastic moduli such as longitudinal modulus, shear modulus, Young's modulus, bulk modulus, Poisson's ratio and hardness of the glass system were discussed.